Kemampuan Kader dan Partisipasi Masyarakat pada Pelaksanaan Program Posyandu di Karangpucung Purwokerto Selatan - Subagyo, Widyo; Mukhadiono, (Jurusan Keperawatan FIKES UNSOED, 2010)
Posyandu Program is very important to support mother and child health. The successful of Posyandu Program needed active role of health cadre and public participation. The aim of the research is to know the relation of cadre ability and public participation with the efectiveness of Posyandu Program at Karangpucung Village Purwokerto Selatan Subdistrict Banyumas Regency. This research was conducted at Karangpucung Village Purwokerto Selatan Subdistrict Banyumas Regency with the target research was the Posyandu Cadre in its village. The research used survey, sampling method used total sampling, data collecting method used intreview, observation, questionnare, and documentation. The data analyzed used correlation of tau c rank Kendall, partial Kendall rank correlation, and Kendall concordance coefficient. The result of this research showed that Cadre ability has significant relation with the efectiveness of Posyandu Program. It proved with t-test value bigger than t-table in level of significance 95% ((3.435 > 2.00). Public participation has significant relation with the efectiveness of Posyandu Program. It proved with t-test value bigger than t-table in level of significance 95% (3.524 > 2.00). Cadre ability and public participation, collectivelly, has significant relation with efectiveness of Posyandu Program. It proved with X2-test value (53.343) bigger than X2-table in level of significance 95% (5.991). Based from the results, so all hypothesis proposed was accepted. Implication of this research is: ability of Cadre Posyandu should be increased continually, especially cadre which not yet followed the specialized training of cadre. Otherwise, elite figure require to be involved to support the activities of Posyandu Program.